Copper foil for polyphenyl ether high-frequency copper-clad plate and preparation method of copper foil
By coating the silicone modified polysenyl alcohol layer containing coupling groups on the surface of the copper foil, the problem of insufficient bonding force between the copper foil and the semi-cured sheet is solved, and the strength and signal transmission performance of the polysenyl alcohol high-frequency copper clad plate are improved.
Patent Information
- Application Number
- CN202411447798.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The prior art has shortcomings in improving the bonding force between the copper foil and the semi-cured sheet, resulting in large loss of signal transmission of copper clad plate under high frequency conditions.
The copper foil is treated with organic layer with silicone modified polysenol containing coupling groups. The modified polysenol solution is formed by copolymerization of hydroxy hydrogen-containing silicone oil, double-ended hydroxy polysenol and diisocyanate. Hydrosilicon addition reaction was carried out under the conditions of anhydrous solvent and an organotin catalyst to obtain a silicone modified polyshenol solution with coupling groups, which was coated on the surface of the copper foil to enhance its binding force with the resin material.
The bonding force between the copper foil and the semi-cured sheet is significantly improved, the strength of the polystyrene alcohol high-frequency copper clad plate is enhanced, and the signal transmission loss under high-frequency conditions is reduced.
Smart Images

Figure CN119432219A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper clad laminates, and particularly relates to a copper foil for a polyphenylene ether high-frequency copper clad laminate and a preparation method thereof. Background Art
[0002] With the development of society, people have higher and higher requirements for high frequency and high speed. The development of blockchain, Internet of Things, cloud computing / servers and smart phones all require the support of high frequency and high speed printed circuit board (PCB) technology. As the main raw material of high frequency and high speed PCB, high frequency and high speed copper clad laminate is the research focus. Copper foil, resin and glass fiber cloth are the three major raw materials of copper clad laminate. Their quality directly affects PCB signal transmission.
[0003] There are many resin materials suitable for the production of high-frequency and high-speed copper-clad laminates, such as polytetrafluoroethylene (PTFE), polyphenylene ether (PPO / PPE), cyanate ester (CE), polyimide (PI), liquid crystal polymer (LCP), etc. The corresponding dielectric properties are polytetrafluoroethylene (PTFE) dielectric constant Dk is 2.1, dielectric loss Df is 0.0005; polyphenylene ether (PPO / PPE) dielectric constant Dk is 2.5, dielectric loss Df is 0.0007; cyanate ester (CE) dielectric constant Dk is 2.9, dielectric loss Df is 0.0030; polyimide ( The dielectric constant Dk of PTFE (PI) is 3.1, and the dielectric loss Df is 0.0028; the dielectric constant Dk of liquid crystal polymer (LCP) is 3.3, and the dielectric loss Df is 0.0020. According to the dielectric properties of each material, it can be seen that PTFE resin has excellent dielectric properties, but the forming process is complicated and the cost is high; the dielectric properties of CE, PI, LCP, etc. are relatively poor, and it is difficult to meet the requirements of higher and higher frequency and high speed. Polyphenylene ether (PPO / PPE) has good dielectric properties and is suitable for hot pressing. The production process is relatively simple, which is suitable for the production of large quantities of high-frequency and high-speed copper clad laminates.
[0004] Copper foil is one of the indispensable basic materials for copper clad laminates and is also a conductive material in PCBs. The characteristics of copper foil have a significant impact on PCB performance, especially when used in high-frequency and high-speed circuit boards. The surface morphology of copper foil has a significant impact on PCB signal transmission loss. At the same time, during the preparation process of copper clad laminates, copper foil and glass fiber cloth semi-cured sheets impregnated with resin are generally obtained by hot pressing, and the bonding force between copper foil and semi-cured sheets directly affects the performance stability of copper clad laminates. The existing method for enhancing the bonding force between copper foil and semi-cured sheets is mainly to treat the surface of copper foil with silane coupling agents to obtain an organic layer with high adhesion to improve the bonding force with resin materials. However, the surface tension difference between the organic polysiloxane layer generated by surface treatment with a simple silane coupling agent and the resin material is still large, resulting in a low bonding force after pressing with the resin material semi-cured sheet. Summary of the invention
[0005] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing copper foil for polyphenylene ether high-frequency copper clad laminate.
[0006] Another object of the present invention is to provide a copper foil for polyphenylene ether high-frequency copper-clad laminate prepared by the above method.
[0007] Another object of the present invention is to provide a polyphenylene ether high-frequency copper-clad laminate prepared by using the copper foil.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing copper foil for polyphenylene ether high-frequency copper-clad laminate comprises the following preparation steps:
[0010] The copper foil is sequentially subjected to anode treatment, heat resistance treatment, oxidation protection treatment and organic transition layer treatment to obtain the copper foil for polyphenylene ether high frequency copper clad laminate;
[0011] The method for treating the organic transition layer is as follows:
[0012] (1) heating hydroxyl hydrogen silicone oil, double-terminated hydroxyl polyphenyl ether and diisocyanate in an anhydrous solvent and an organic tin catalyst to copolymerize to obtain a hydrogen-containing polysiloxane-modified polyphenyl ether solution;
[0013] (2) adding a vinyl silane coupling agent and a chloroplatinic acid catalyst to the hydrogenated polysiloxane-modified polyphenylene ether solution of step (1), removing water with nitrogen, and then heating to carry out a hydrosilylation reaction to obtain a silicone-modified polyphenylene ether solution containing a coupling group;
[0014] (3) coating the organic silicon modified polyphenylene ether solution containing coupling groups obtained in step (2) on the surface of the copper foil after anti-oxidation treatment, drying and curing, and obtaining an organic transition layer.
[0015] Preferably, the structural formula of the hydroxyl hydrogen-containing silicone oil is as follows:
[0016] In the formula, m is an integer of 2 to 50, and n is an integer of 0 to 50.
[0017] The above-mentioned hydroxyl hydrogen silicone oil is a conventional raw material in the art, which can be obtained by ring-opening polymerization of a hydrogen-containing ring body (D4H) without adding a capping agent or with a small amount of water as a capping agent, or by ring-opening copolymerization of a hydrogen-containing ring body (D4H) and methylcyclosiloxane (D4).
[0018] Preferably, the structural formula of the double-terminated hydroxyl polyphenylene ether is as follows:
[0019] In the formula, a is an integer of 5 to 30.
[0020] The above-mentioned double-terminated hydroxyl polyphenylene ether is a conventional raw material in the art.
[0021] Preferably, the diisocyanate is toluene diisocyanate, isophorone diisocyanate, phenylmethane diisocyanate, dicyclohexylmethane diisocyanate, or hexamethylene diisocyanate.
[0022] Preferably, the anhydrous solvent is dimethylformamide, N-methylpyrrolidone, dichloromethane, toluene, xylene, ethyl acetate; the organic tin catalyst is dibutyltin dilaurate; and the temperature of the heated copolymerization reaction is 50-80°C.
[0023] More preferably, the specific preparation steps of the hydrogen-containing polysiloxane-modified polyphenylene ether solution are as follows:
[0024] First, hydroxyl hydrogen silicone oil and diisocyanate are added to an anhydrous solvent in a molar ratio of 1:2-3 to dissolve evenly, then an organic tin catalyst is added and the temperature is raised to 50-80°C to react to obtain an isocyanate group-containing prepolymer; then, dihydroxyl polyphenyl ether is added and stirred to react, the molar ratio of dihydroxyl polyphenyl ether to hydroxyl hydrogen silicone oil is 1-2:1 to obtain a hydrogenated polysiloxane modified polyphenyl ether solution.
[0025] Preferably, the amount of the vinyl silane coupling agent added is 0.4 to 1.2 times the molar amount of silicon and hydrogen in the hydrogen-containing polysiloxane-modified polyphenylene ether.
[0026] The reaction scheme involved in the preparation process of the organosilicon-modified polyphenylene ether containing coupling groups of the present invention is as follows: Figure 1 shown.
[0027] Preferably, the anode treatment refers to electroplating anode treatment using an electrolyte containing copper sulfate, sulfuric acid, sodium stannate and glucose, and the current density of the anode treatment is 5 to 20A / dm 2 The anode treatment time is 1 to 10 seconds; the heat-resistant treatment refers to the electroplating coating heat-resistant layer treatment using an electrolyte containing zinc sulfate, indium sulfate and potassium sodium tartrate, and the current density of the heat-resistant treatment is 0.1 to 2A / dm 2 The anti-oxidation treatment refers to electroplating with a chromium plating solution, the pH of the anti-oxidation treatment is 2 to 6, and the current density is 1 to 5A / dm 2 .
[0028] A copper foil for polyphenylene ether high-frequency copper-clad laminate is prepared by the method.
[0029] A polyphenylene ether high-frequency copper-clad laminate prepared by using the copper foil is obtained by hot-pressing a glass fiber cloth prepreg impregnated with polyphenylene ether resin and the copper foil.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention uses silicone-modified polyphenylene ether containing coupling groups to perform organic layer treatment on the pretreated copper foil. Compared with conventional silane coupling agents, the present invention has better bonding strength with the polyphenylene ether resin impregnated prepreg and more stable performance.
[0032] (2) The polyphenylene ether high-frequency copper-clad laminate prepared using the copper foil of the present invention has higher strength and can resist the surface deformation and increased roughness of the copper foil caused by stress, thereby reducing signal transmission loss under high-frequency conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a reaction route diagram involved in the preparation process of the organosilicon-modified polyphenylene ether containing coupling groups. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0035] Example 1
[0036] A copper foil for a polyphenylene ether high-frequency copper-clad laminate and a method for preparing a polyphenylene ether high-frequency copper-clad laminate, comprising the following preparation steps:
[0037] (1) The raw copper foil was placed in an electrolyte containing 80 g / L copper sulfate, 120 g / L sulfuric acid, 0.05 g / L sodium stannate, and 4 g / L glucose at 12 A / dm 2 The anode treatment was carried out with a current density of , and the anode treatment time was 5s.
[0038] (2) The copper foil obtained in step (1) was electroplated at 1.2 A / dm using an electroplating solution containing 55 g / L zinc sulfate, 0.04 g / L indium sulfate, and 80 g / L potassium sodium tartrate. 2 The electroplating treatment is carried out at a current density of to obtain a copper foil coated with a heat-resistant layer.
[0039] (3) The copper foil obtained in step (2) was plated with a chromium plating solution having a chromium ion concentration of 5 g / L at a temperature of 1.5 A / dm 2 The electroplating treatment was carried out at a current density of , and the pH of the electroplating treatment was 4.5 to obtain a copper foil coated with an anti-oxidation layer.
[0040] (4) The copper foil obtained in step (3) is surface-coated with a solution of organosilicon-modified polyphenylene ether containing coupling groups, and then vacuum-dried and solidified, and the solvent is recovered to obtain a copper foil for a polyphenylene ether high-frequency copper-clad laminate.
[0041] (5) subjecting the copper foil obtained in step (4) to a heat pressing treatment with a glass fiber cloth semi-cured sheet impregnated with a polyphenylene ether resin, wherein the heat pressing treatment temperature is 160 to 180° C., the pressure is 15 MPa, and the time is 90 min to obtain a polyphenylene ether high-frequency copper clad laminate.
[0042] The organosilicon-modified polyphenylene ether solution containing coupling groups is prepared by the following method:
[0043] 1) Hydroxy-hydrogenated silicone oil (hydroxyl value of 1wt%, hydrogen content of 0.90wt%, average molecular weight of 3500) and toluene diisocyanate are added to a toluene solvent in a molar ratio of 1:2.5 to dissolve evenly, then dibutyltin dilaurate is added as a catalyst, the temperature is raised to 60°C for reaction for 3h, and the hydroxyl content of the product is detected to be less than 0.02%, thereby obtaining an isocyanate-containing prepolymer; then a dihydroxy-terminated polyphenylene ether (average molecular weight of 2100) is added, the temperature is raised to 80°C, and the stirring reaction is continued for 2h, the molar ratio of the dihydroxy-terminated polyphenylene ether to the hydroxy-hydrogenated silicone oil is 1.5:1, and a hydrogenated polysiloxane-modified polyphenylene ether solution is obtained (the average molecular weight of the sampled product is 46000, the hydroxyl value is 0.03wt%, the isocyanate content is 0.05wt%, and the silicon hydrogen content is 0.44wt%).
[0044] 2) Adding a vinyl triethoxysilane coupling agent and a chloroplatinic acid catalyst to the hydrogenated polysiloxane-modified polyphenylene ether solution of step 1), wherein the amount of the vinyl triethoxysilane coupling agent added is 0.6 times the molar amount of silicon and hydrogen, heating to 90° C. for a silicon hydrogen addition reaction for 4 h after dehydration with nitrogen, and detecting the silicon hydrogen content of the product to be 0.14 wt %, to obtain a silicone-modified polyphenylene ether solution containing a coupling group.
[0045] Example 2
[0046] A copper foil for a polyphenylene ether high-frequency copper-clad laminate and a method for preparing a polyphenylene ether high-frequency copper-clad laminate. Compared with Example 1, the organosilicon-modified polyphenylene ether solution containing a coupling group is prepared by the following method:
[0047] 1) Hydroxy-hydrogenated silicone oil (hydroxyl value of 3.2wt%, hydrogen content of 1.5wt%, average molecular weight of 1000) and isophorone diisocyanate are added to a toluene solvent in a molar ratio of 1:2 to dissolve evenly, then dibutyltin dilaurate is added as a catalyst and the temperature is raised to 60°C for reaction for 3h, and the hydroxyl content of the product is detected to be less than 0.02%, thereby obtaining an isocyanate-containing prepolymer; then a dihydroxy-terminated polyphenylene ether (average molecular weight of 1500) is added, the temperature is raised to 80°C and the reaction is continued with stirring for 2h, the molar ratio of the dihydroxy-terminated polyphenylene ether to the hydroxy-hydrogenated silicone oil is 1:1, and a hydrogenated polysiloxane-modified polyphenylene ether solution is obtained (the average molecular weight of the sampled product is 35000, the hydroxyl value is 0.04wt%, the isocyanate content is 0.07wt%, and the silicon hydrogen content is 0.51wt%).
[0048] 2) Adding a vinyl triethoxysilane coupling agent and a chloroplatinic acid catalyst to the hydrogenated polysiloxane-modified polyphenylene ether solution of step 1), wherein the amount of the vinyl triethoxysilane coupling agent added is 0.4 times the molar amount of silicon and hydrogen, heating to 90° C. for a silicon-hydrogen addition reaction for 4 hours after dehydration with nitrogen, and detecting the silicon-hydrogen content of the product to be 0.22 wt %, to obtain a silicone-modified polyphenylene ether solution containing a coupling group.
[0049] Example 3
[0050] A copper foil for a polyphenylene ether high-frequency copper-clad laminate and a method for preparing a polyphenylene ether high-frequency copper-clad laminate. Compared with Example 1, the organosilicon-modified polyphenylene ether solution containing a coupling group is prepared by the following method:
[0051] 1) Hydroxyl hydrogen silicone oil (hydroxyl value of 0.64wt%, hydrogen content of 0.8wt%, average molecular weight of 5000) and hexamethylene diisocyanate are added to toluene solvent in a molar ratio of 1:3 to dissolve evenly, then dibutyltin dilaurate catalyst is added and the temperature is raised to 60°C for reaction for 3h, and the hydroxyl content of the product is detected to be less than 0.02%, thereby obtaining an isocyanate group-containing prepolymer; then dihydroxy-terminated polyphenylene ether (average molecular weight of 3000) is added, the temperature is raised to 80°C and the stirring reaction is continued for 2h, the molar ratio of dihydroxy-terminated polyphenylene ether to hydroxy hydrogen silicone oil is 2:1, and a hydrogen-containing polysiloxane-modified polyphenylene ether solution is obtained (the average molecular weight of the sampled product is 51000, the hydroxyl value is 0.03wt%, the isocyanate content is 0.06wt%, and the silicon hydrogen content is 0.32wt%).
[0052] 2) Adding a vinyl triethoxysilane coupling agent and a chloroplatinic acid catalyst to the hydrogenated polysiloxane-modified polyphenylene ether solution of step 1), wherein the amount of the vinyl triethoxysilane coupling agent added is 0.8 times the molar amount of silicon and hydrogen, heating to 90° C. for a silicon hydrogen addition reaction for 4 h after dehydration with nitrogen, and detecting the silicon hydrogen content of the product to be 0.08 wt%, to obtain a silicone-modified polyphenylene ether solution containing a coupling group.
[0053] Comparative Example 1
[0054] Compared with Example 1, this comparative example uses an equal amount of vinyl triethoxysilane coupling agent solution to replace the organosilicon-modified polyphenylene ether solution containing coupling groups in step (4) to perform surface coating treatment on the copper foil, and the rest is the same.
[0055] Comparative Example 2
[0056] Compared with Example 1, this comparative example directly uses an equal amount of the hydrogenated polysiloxane-modified polyphenylene ether solution of step 1) to replace the organosilicon-modified polyphenylene ether solution containing coupling groups in step (4) to carry out surface coating treatment on the copper foil, and the rest is the same.
[0057] The bonding force, bending strength and signal transmission loss at high frequency (20 GHz) of the polyphenylene ether high-frequency copper clad laminates obtained in the above embodiments and comparative examples were tested, and the results are shown in Table 1 below.
[0058] Table 1
[0059] Test cases / performance Binding force (kgf / cm) Bending strength(MPa) Signal transmission loss (dB / in) Example 1 1.35 283 23 Example 2 1.41 257 28 Example 3 1.36 279 25 Comparative Example 1 0.92 210 39 Comparative Example 2 0.85 246 35
[0060] From the comparison results of the above embodiments and comparative example 1, it can be seen that the present invention uses organic silicon modified polyphenylene ether containing coupling groups to treat the pretreated copper foil with an organic layer, which has better bonding force and higher bending strength with the polyphenylene ether resin impregnated prepreg than conventional silane coupling agents, and can significantly reduce the signal transmission loss of the obtained polyphenylene ether copper clad laminate under high frequency conditions. From the results of comparative example 2, it can be seen that the bending strength of the obtained copper clad laminate is significantly improved compared with conventional silane coupling agents by using polysiloxane modified polyphenylene ether without coupling groups for treatment, but due to the lack of coupling groups that form a good bond with the inorganic treatment layer copper foil, the bonding force is significantly reduced, and the effect of reducing the signal transmission loss is not as good as that of the embodiment.
[0061] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing copper foil for polyphenylene ether high-frequency copper-clad laminate, characterized in that: The method comprises the following preparation steps: The copper foil is sequentially subjected to anode treatment, heat resistance treatment, oxidation protection treatment and organic transition layer treatment to obtain the copper foil for polyphenylene ether high frequency copper clad laminate; The method for treating the organic transition layer is as follows: (1) heating hydroxyl hydrogen silicone oil, double-terminated hydroxyl polyphenyl ether and diisocyanate in an anhydrous solvent and an organic tin catalyst to copolymerize to obtain a hydrogen-containing polysiloxane-modified polyphenyl ether solution; (2) adding a vinyl silane coupling agent and a chloroplatinic acid catalyst to the hydrogenated polysiloxane-modified polyphenylene ether solution of step (1), removing water with nitrogen, and then heating to carry out a hydrosilylation reaction to obtain a silicone-modified polyphenylene ether solution containing a coupling group; (3) coating the organic silicon modified polyphenylene ether solution containing coupling groups obtained in step (2) on the surface of the copper foil after anti-oxidation treatment, drying and curing, and obtaining an organic transition layer.
2. The method for preparing a copper foil for a polyphenylene ether high-frequency copper-clad laminate according to claim 1, characterized in that: The structural formula of the hydroxyl hydrogen-containing silicone oil is as follows: In the formula, m is an integer of 2 to 50, and n is an integer of 0 to 50.
3. The method for preparing a copper foil for a polyphenylene ether high-frequency copper-clad laminate according to claim 1, characterized in that: The structural formula of the double-terminated hydroxyl polyphenylene ether is as follows: In the formula, a is an integer of 5 to 30.
4. The method for preparing a copper foil for a polyphenylene ether high-frequency copper-clad laminate according to claim 1, characterized in that: The diisocyanate is toluene diisocyanate, isophorone diisocyanate, phenylmethane diisocyanate, dicyclohexylmethane diisocyanate, and hexamethylene diisocyanate.
5. The method for preparing a copper foil for a polyphenylene ether high-frequency copper-clad laminate according to claim 1, characterized in that: The anhydrous solvent is dimethylformamide, N-methylpyrrolidone, dichloromethane, toluene, xylene, and ethyl acetate; the organic tin catalyst is dibutyltin dilaurate; and the temperature of the heating copolymerization reaction is 50-80°C.
6. The method for preparing a copper foil for a polyphenylene ether high-frequency copper-clad laminate according to claim 1, characterized in that: The specific preparation steps of the hydrogen-containing polysiloxane-modified polyphenylene ether solution are as follows: First, hydroxyl hydrogen silicone oil and diisocyanate are added to an anhydrous solvent in a molar ratio of 1:2-3 to dissolve evenly, then an organic tin catalyst is added and the temperature is raised to 50-80°C to react to obtain an isocyanate group-containing prepolymer; then, dihydroxyl polyphenyl ether is added and stirred to react, the molar ratio of dihydroxyl polyphenyl ether to hydroxyl hydrogen silicone oil is 1-2:1 to obtain a hydrogenated polysiloxane modified polyphenyl ether solution.
7. The method for preparing a copper foil for a polyphenylene ether high-frequency copper-clad laminate according to claim 1, characterized in that: The amount of the vinyl silane coupling agent added is 0.4 to 1.2 times the molar amount of silicon and hydrogen in the hydrogen-containing polysiloxane-modified polyphenylene ether.
8. The method for preparing a copper foil for a polyphenylene ether high-frequency copper-clad laminate according to claim 1, characterized in that: The anode treatment refers to electroplating anode treatment using an electrolyte containing copper sulfate, sulfuric acid, sodium stannate and glucose, and the current density of the anode treatment is 5 to 20A / dm 2 The anode treatment time is 1 to 10 seconds; the heat-resistant treatment refers to the electroplating coating heat-resistant layer treatment using an electrolyte containing zinc sulfate, indium sulfate and potassium sodium tartrate, and the current density of the heat-resistant treatment is 0.1 to 2A / dm 2 The anti-oxidation treatment refers to electroplating with a chromium plating solution, the pH of the anti-oxidation treatment is 2 to 6, and the current density is 1 to 5A / dm 2 .
9. A copper foil for a polyphenylene ether high-frequency copper-clad laminate, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. A polyphenylene ether high frequency copper clad laminate, characterized in that: The invention is obtained by hot pressing and compounding a glass fiber cloth semi-cured sheet impregnated with polyphenylene ether resin and the copper foil as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing dihydroxy-terminated polyphenylene oxide in aqueous medium and product as well as application thereof
CN102604075A
Method for preparing silicon containing di-hydroxyl polyphenyl ether through organosilicone modification and application of product
CN105315454A
Epoxy group-containing organosilicon modified poly(phenylene oxide) resin as well as a preparation method and application thereof
CN109988299A
Polyphenylene oxide resin, method of preparing polyphenylene oxide resin, polyphenylene oxide prepolymer and resin composition
US20160185904A1
Copper clad laminate and print circuit board comprising the same
US20210368628A1